Promoción de Paquetes Turísticos mediante un Blog Interactivo para incentivar el Turismo Interno de Estudiantes del último año de Secundaria - Zambrano Fuentes, Catherine Denisse (2013)
One of the source where you can find all type of information, is the internet this lets us navigate in a rapid way to anywhere in the world. Promoting any type of products is another function that allows the internet and where it promotes tourist's destinations in Ecuador, with the purpose that the people find the best options that will be of their need. The last year of college phase ends with a graduation trip, where offering the best options of the tourist's intern packets, they can decide what option adjusts in a positive way to share the lasts experiences like students before going to a university phase. The tourist development in the country has captures the interest of people to travel within the country in search of new adventures and relaxation, that is why its recommended according their demands , a large lists of options where to visit in every holiday. With the different types of blogs that the web offers you can create one according to the needs that you have or the information that you wish to share in a rapid and comfortable way. This is why students are able to find options of intern packages to establish their trip.